Making Better Dose Decisions: Using Exposure‐Response Modeling to Integrate Efficacy Outcome of Two Phase IIb Clinical Trials of Ubrogepant for Migraine Treatment - Chi‐Chung Li; Tiffini Voss; Ken Kowalski; Bei Yang; Huub Jan Kleijn; Christopher J. Jones; Rolien Bosch; David Michelson; Matthew DeAngelis; Yang Xu; Iris Xie; Prajakti A. Kothare (Wiley, 2020)
Ubrogepant (MK‐1602) is a novel, oral, calcitonin gene‐related peptide receptor antagonist in clinical development with positive phase III outcomes for acute treatment of migraine. This paper describes the population exposure‐response (E‐R) modeling and simulations, which were used to inform the phase III dose‐selection rationale, based on ~ 800 participants pooled across two phase IIb randomized dose‐finding clinical trials. The E‐R model describes the placebo and ubrogepant treatment effects based on migraine pain end points (2‐hour pain relief and 2‐hour pain freedom) at various dose levels. Sensitivity analyses were conducted to evaluate various assumptions of placebo response in light of the high placebo response observed in one phase II trial. A population pharmacokinetic model describing the effect of formulations was included in the E‐R simulation framework to assess potential dose implications of a formulation switch from phase II to phase III. Model‐based simulations predict that a dose of 25 mg or higher is likely to achieve significantly better efficacy than placebo with desirable efficacy levels. The understanding of E‐R helped support the dose selection for the phase III clinical trials.